Reflecting Staff Reward in Employee Output: A Validation of Henri Fayol's 7th Principle of Management Using Nigerian Manufacturing Sector - Ikwuo, Ama Kalu; Nwite, Isaiah Michael; Ogechukwu Nworie, Gilbert (Manunggal Halim Jaya, 2025)
An inadequate employee reward system is one of the key reasons many employees approach their tasks with diminished enthusiasm, reduced focus, and inefficiency, which eventually hinders their productivity and undermines the overall success of the organization. To address the above problem, this study examined the effect of staff reward on the output of employees in Nigerian manufacturing firms thereby testing Henri Fayol's 7th Principle of Management. Specifically, the extent to which employee remuneration affects the value added of listed manufacturing firms in Nigeria was assessed, based on an ex-post facto research design. Purposive sampling was used in selecting a sample size of fifty-five out of the sixty-four listed manufacturing firms in Nigeria. Secondary data were collected from the annual reports of the firms between 2015 – 2023 accounting periods. Hypothesis was tested using panel estimated generalised least square with cross-section weights that addressed both heteroskedasticity and cross-sectional dependence. It was found that: staff reward significantly enhances employee output among listed manufacturing firms in Nigeria (β = 3.954302; p-value = 0.0000), aligning with the theoretical framework provided by Henri Fayol's 7th principle. In conclusion, an optimized reward system enhances organizational productivity by boosting employee engagement, as investing in staff rewards is a strategic move that improves performance and supports growth. Premised on this conclusion, we recommend that manufacturing firms should focus on designing compensation packages that are competitive within the industry, incorporate performance-based bonuses, and provide non-monetary incentives such as career development opportunities and recognition programs.